MSME Tax Implementation on MSME Taxpayer Compliance - Sumardi Adiman; Miftha Rizkina (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to determine how the level of compliance of MSME taxpayers after the change in PP No. 46 of 2013 to PP No. 23 of 2018. This research uses a descriptive qualitative approach with data collection techniques using interview and questionnaire methods using primary data. The results showed that almost some MSME already know the MSME tax regulations, both the old and the new regulations, so that MSME actors can understand the sanctions imposed on MSME and can affect the growth rate of MSME taxpayer compliance.